A educação especial no município de Porto Ferreira-SP: 1972 a 2011 - Loureiro, Aline Dozzi Tezza (2013)
The number of students with disabilities in schools is increasing every year due to government support, both for the public school as to private institutions. Thinking about it, this research was carried out to understand the organization and operation of Special Education in Porto Ferreira, Brazil. The authors substantiate this research work in a critical perspective (Saviani, Januzzi, Ferraro, Gatti). Methodology used in document analysis of all documents relating to special education in the municipality (laws, decrees, minutes of meetings, newspaper accounts municipal, school census data), as well as the use of interviewing people related to special education. The results point towards: a) the importance of the private institution, the philanthropic (Association of Parents and Friends of Handicapped-APAE) has since its inception until the present day, b) the absence of a project political intended for students with disabilities in primary schools in the municipality, c) the "absence" of a social movement of persons with disabilities in the county searched.